The Philosophy of The Objectives of Islamic Law with a Systems Approach: Study of Jasser's Thought in The Book of Maqashid Ash-Shari'ah Kafalsafah Li At-Tasyri' Al-Islami Ru'yah Mandhumiyah - Ahmad Musadad; Achmad Badarus Syamsi; Umi Indasyah Zahro; A. Mufti Khazin; Baihaqi Baihaqi; Tri Pujiati; Imamuddin Imamuddin (Nuris Journal of Education and Islamic Studies, 2026)
This study explores the philosophical foundations of the objectives of Islamic law (maqāṣid al-sharī‘ah) through a systems approach as articulated by Jasser Auda in his work Maqāṣid Asy-Syarī‘ah Kafalsafah li At-Tasyri‘ Al-Islāmī: Ru’yah Mandhumiyah. The urgency of this research lies in the increasing demand to reinterpret Islamic law in order to address the complexities of contemporary society while maintaining its foundational principles. This study employs a qualitative method with a library research approach, focusing on Auda’s conceptual framework and its implications for the philosophy of Islamic law. The findings reveal that Auda’s systems approach redefines maqāṣid as a dynamic and holistic framework emphasizing justice, public interest, and human dignity. This perspective challenges rigid textual interpretations and proposes a flexible methodology that aligns Islamic law with the realities of modern life. Auda’s approach significantly contributes to contemporary discourse on Islamic jurisprudence by presenting maqāṣid as a living philosophy capable of adapting to evolving societal contexts